The Integration of Islamic Social Finance Towards Accelerating Economic Development in Malaysia - Mahadi, Nur Farhah (El-Barka Journal of Islamic Economics and Business, 2025)
This study constructs a comprehensive framework for an integrated Islamic social finance model in Malaysia, exploring how instruments like zakāt, waqf, Islamic microfinance, and Islamic crowdfunding (e.g. ṣadaqah, infāq, and hibah) rooted in principles of Maqāṣid al-Sharīʽah can accelerate Malaysian economic development and foster a prosperous and inclusive society by aligning with key national blueprints such as the Shared Prosperity Vision 2030, Twelfth Malaysia Plan (12MP),  and the MADANI Economy framework. This study adopts a qualitative approach, it undertakes a comprehensive desk-based review of academic and institutional literature to perform a thematic and content analysis, aiming to construct a conceptual framework for an integrated Islamic social finance system in Malaysia and propose its application to accelerate economic development by supporting vulnerable populations. This study reveals that the synergy of Islamic social finance instruments is poised to enhance Malaysia's MADANI Economy framework, fostering a progressive and prosperous nation by aligning with national policies and the Sustainable Development Goals (SDGs), and thereby elevating both economic competitiveness and citizens’ quality of life through the collaborative efforts of key public and private stakeholders. In conclusion, this study articulates an integrated Islamic social finance framework, emphasizing the collaborative potential of key Malaysian government and financial institutions to foster a just and prosperous nation by empowering vulnerable communities and aligning economic development with sustainable, inclusive principles, thereby positioning Malaysia as a global leader in an integrated Islamic social finance framework.